EFEKTIVITAS COOKIES UBI JALAR UNGU DALAM MENINGKATKAN KADAR HEMOGLOBIN DAN HEMATOKRIT PADA REMAJA PUTRI ANEMIA - Nusra, ST Austa; Lestari, Anik; Hikmayani, Nur Hafidha (Poltekkes Kemenkes Bandung, 2025)
Adolescent girls are susceptible to anemia due to menstruation, less diverse food intake, causing hemoglobin and hematocrit levels below normal. The global prevalence of anemia in women aged 15-49 years is 29.9%, especially in Indonesia aged 15-24 years is 48.9%. Therefore, it is necessary to overcome anemia with functional purple sweet potato (UJU) food produced into cookies to increase Fe intake and can extend shelf life. This study aimed to assess the effectiveness of UJU cookies in increasing Hb and Hct levels in adolescent girls. This experiment used a pre-post test design with a control group. The sampling technique used the stratified random sampling method. The research respondents were 38 adolescent girls from 3 high schools in Surakarta City with three treatment groups. The volumetric impedance method for measuring Hb and Hct. The research intervention in the form of UJU cookies and regular cookies was given for 60 days. The Kruskal-Wallis test and one way Anova were used to compare Hb and Hct levels between the three groups. The results showed that the provision of UJU cookies 100 g/week (P2) experienced an increase in Hb of 0.52 g/dL (p = 0.001) and Hct levels increased by 4.04% (p = 0.001). From this study it can be concluded that the provision of UJU cookies can improve Hb and Hct levels in anemic adolescent girls and as an alternative based on functional food to increase Hb, Hct levels and nutrient intake so that it can overcome the problem of anemia in the community, especially adolescent girls.